Peranan Guru Pendidikan Agama Islam Dalam Membiasakan Shalat Berjamaah Bagi Siswa SMA Aksara Bajeng - St.Sahwa Mutaqaddima; Abd. Rahman Bahtiar; Sitti Satriani (Advances In Education Journal, 2025)
This study aims to (1) describe the practice of habituating congregational prayer at SMA Aksara Bajeng, (2) examine the role of Islamic Education teachers in fostering students’ habit of performing congregational prayer, and (3) identify the supporting factors that contribute to the success of habituating congregational prayer among students. This research employs a field study approach located at Jl. Batang Banoa No. 31, Mata Allo Village, Bajeng District, using a descriptive qualitative method. Data were collected directly from the field through observation, interviews, and documentation. The findings show that (1) the process of habituating congregational prayer at SMA Aksara Bajeng has been implemented well, although some students still lack intrinsic awareness to participate, influenced by family and school environment factors. (2) The role of Islamic Education teachers includes serving as motivators who encourage students to perform congregational prayers consistently, as role models who set examples through knowledge, character, and behavior, as mentors who provide guidance, advice, and direction, and as evaluators who assess both students’ progress and the effectiveness of the learning process. (3) The factors supporting the success of congregational prayer habituation include students’ internal motivation, parental support, adequate prayer facilities, a supportive school environment, and strong collaboration among teachers.